Propuesta para la implementación de postres tradicionales en la empresa “Five” minimarket de la ciudad de Otavalo - Cabascango Anrango, Richard Jonathan (2023)
The city of Otavalo is known for its diverse culture and historical heritage, visible in local festivals and traditions. Its clothing, food and Kichwa dialect are clear expressions of its cultural identity. Despite the importance of its traditional confectionery, there is little accurate information about it in books and theses. The research hypothesized that there are few sources of information and that they generalize referring to the culinary history of Ecuador, in this framework a study was carried out to better understand the Otavaleño confectionery. We sought to collect, analyze and synthesize all possible information, so the study showed that, although some of these desserts have a long tradition, there is a shortage of reliable and verifiable scientific data, which is why applying this research and record it helped to determine which are the traditional Otavalo desserts and thus proceed to propose the implementation of a line of traditional handmade desserts in the company 'FIVE' minimarket in the city of Otavalo, through innovation of the current gastronomic offer. In the research process, three fundamentals were identified that argue the belonging of certain traditional desserts of Otavalo, which are the following: first, the time that the preparations have been perpetuated, second, the reputation of the preparations on important holidays such as Pawkar Raymi, Inti Raymi and Yamor and third, the techniques, methods and tools used for the preparations. The methodology of the present investigation is of a mixed type and as a result objective foundations were obtained which support the belonging of traditional desserts in Otavalo, this is due to the contribution of the documentary information found that is generalized to a country, and to the field investigation that was synthesized and concluded to a single criterion.